2021
DOI: 10.1002/pat.5208
|View full text |Cite
|
Sign up to set email alerts
|

Itaconimide telechelics of polyethers, synthesis, and their impact on mechanical properties of unsaturated polyester resins

Abstract: The present work focuses on the evolution in the mechanical properties of an unsaturated polyester resin (UPR) on blending with itaconimide‐end terminated polyethers, namely, polypropylene glycol (I‐PPG), polyethylene glycol (I‐PEG), and polytetra methylene oxide (I‐PTMO). Blends of an unsaturated polyester (UPR, based on propylene glycol, terephthalic, and maleic acids) resin with different loading of itaconimide end‐capped telechelics were investigated for their mechanical and thermal properties. Blending wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In previous works, maleimide-and itaconimide end-capped polyethers were chosen as the reactive oligomers. [16,17] The toughening effect was found to depend not only on the nature of the polyether but also on its concentration in the blend as well as how the end groups react or copolymerize with styrene/maleic groups. The reactivity of the end group of the polyether with styrene decides the spatial distribution of the polyether in the cured matrix.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous works, maleimide-and itaconimide end-capped polyethers were chosen as the reactive oligomers. [16,17] The toughening effect was found to depend not only on the nature of the polyether but also on its concentration in the blend as well as how the end groups react or copolymerize with styrene/maleic groups. The reactivity of the end group of the polyether with styrene decides the spatial distribution of the polyether in the cured matrix.…”
Section: Resultsmentioning
confidence: 99%
“…In this backdrop, we examined maleic and itaconic end-capped polyethers and found that the terminal group does have an important role in deciding the toughening of the UPER. [16,17] It is of interest to see the impact of these polyethers when nadimide becomes their end group. Nadimide possesses an isolated unsaturation in its backbone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many other glycols and anhydrides or acids can be used to alter the character of unsaturated polyesters. E.g., terephthalic acid and isophthalic acid are chosen to obtain much better chemical and thermal resistance, whereas longchain aliphatic acids, such as succinic acid or adipic acid, enhance the flexibility but reduce the thermal and chemical resistance [10,11].…”
Section: Introductionmentioning
confidence: 99%